Control systems for small hydropower plants: a review. (26th February 2007) - Goyal, Himani; Bhatti, T.S.; Kothari, D.P.
Hydropower is emerging as a major contributor to world energy requirement. It is inexhaustible, clean and has many other benefits like flood mitigation, water supply, irrigation, etc. However, large-scale hydropower generation suffers from inherent disadvantages, such as massive financial outlays, long gestation periods, geological surprises, environmental factors and rehabilitation of the displaced population. Small power hydrostations, being devoid of these problems have become a viable alternative. Control systems and governors are key components of small hydropower stations as they have to supply stable power while accommodating varying load conditions and erratic water flows. They may also be required to operate in a 'stand-alone' mode i.e., not connected to any grid. This paper examines the role, functioning and design of control systems for small hydropower stations. The characteristics of control systems and traditional and modern designs of governors are discussed. Recent technological advances in the field of governors and control systems are discussed subsequently.